Предмет: Алгебра, автор: dimontop2005

Решите пожалуйста!
2у + у(3 – (у + 1)) = у(2 – у) + 12

7 + 3(- х – 3(х + 5)) = 5(7 –

2х) + х



dimontop2005: 1) 2у + у(3 – (у + 1)) = у(2 – у) + 12
dimontop2005: 2) 7 + 3(- х – 3(х + 5)) = 5(7 –2х) + х

Ответы

Автор ответа: Anitazharik
1

1.  2у + у(3 – (у + 1)) = у(2 – у) + 12  

2у + у(3 – у - 1) = 2y - y² +12

2у + 3y - y² - y = 2y - y² +12

2у + 3y - y² - y - 2y + y² = 12

2y = 12

y = 12 : 2

y = 6

2.  7 + 3(- х – 3(х + 5)) = 5(7 – 2х) + х

7 + 3(- х – 3х - 15) = 35 - 10x + x

7 - 3x - 9x - 45 = 35 - 10x + x

10x - x - 3x - 9x  = 35 - 7 + 45

-3x = 73

-x = 73 : 3

-x ≈ 24,3

x ≈ - 24,3


dimontop2005: Спасибо большое!
Anitazharik: пожалуйста
Похожие вопросы
Предмет: Литература, автор: pavelkarpov95